Gene therapy for lysosomal storage diseases: Current clinical trial prospects - Kido, Jun; Sugawara, Keishin; Nakamura, Kimitoshi (Frontiers in Genetics, 2023)
Lysosomal storage diseases (LSDs) are a group of metabolic inborn errors caused by defective enzymes in the lysosome, resulting in the accumulation of undegraded substrates. LSDs are progressive diseases that exhibit variable rates of progression depending on the disease and the patient. The availability of effective treatment options, including substrate reduction therapy, pharmacological chaperone therapy, enzyme replacement therapy, and bone marrow transplantation, has increased survival time and improved the quality of life in many patients with LSDs. However, these therapies are not sufficiently effective, especially against central nerve system abnormalities and corresponding neurological and psychiatric symptoms because of the blood-brain barrier that prevents the entry of drugs into the brain or limiting features of specific treatments. Gene therapy is a promising tool for the treatment of neurological pathologies associated with LSDs. Here, we review the current state of gene therapy for several LSDs for which clinical trials have been conducted or are planned. Several clinical trials using gene therapy for LSDs are underway as phase 1/2 studies; no adverse events have not been reported in most of these studies. The administration of viral vectors has achieved good therapeutic outcomes in animal models of LSDs, and subsequent human clinical trials are expected to promote the practical application of gene therapy for LSDs.